Loss of glyoxalase 2 alters the glucose metabolism in zebrafish - Tabler, Christoph Tobias; Lodd, Elisabeth; Bennewitz, Katrin; Heim, Chiara; Erben, Vanessa; Schröder, Hannes; Poth, Tanja; Fleming, Thomas; Morgenstern, Jakob; Haußer-Siller, Ingrid; Sticht, Carsten; Poschet, Gernot; et al. (Redox Biology, 2023)
Glyoxalase 2 is the second enzyme of the glyoxalase system, catalyzing the detoxification of methylglyoxal to d-lactate via SD-Lactoylglutathione. Recent in vitro studies have suggested Glo2 as a regulator of glycolysis, but if Glo2 regulates glucose homeostasis and related organ specific functions in vivo has not yet been evaluated. Therefore, a CRISPR-Cas9 knockout of glo2 in zebrafish was created and analyzed. Consistent with its function in methylglyoxal detoxification, SD-Lactoylglutathione, but not methylglyoxal accumulated in glo2−/− larvae, without altering the glutathione metabolism or affecting longevity. Adult glo2−/− livers displayed a reduced hexose concentration and a reduced postprandial P70-S6 kinase activation, but upstream postprandial AKT phosphorylation remained unchanged. In contrast, glo2−/− skeletal muscle remained metabolically intact, possibly compensating for the dysfunctional liver through increased glucose uptake and glycolytic activity. glo2−/− zebrafish maintained euglycemia and showed no damage of the retinal vasculature, kidney, liver and skeletal muscle. In conclusion, the data identified Glo2 as a regulator of cellular energy metabolism in liver and skeletal muscle, but the redox state and reactive metabolite accumulation were not affected by the loss of Glo2.